2008
DOI: 10.1111/j.1741-6612.2008.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful ageing by whose definition? Views of older, spiritually affiliated women

Abstract: Conclusions: Participants' multidimensional views of successful ageing were broader than Rowe and Kahn's model and included the need to have a degree of autonomy over the place and manner of the last phase of life and final days (successful dying).Key words: older women, spirituality, successful ageing. IntroductionThe protean concept of 'successful ageing' emerged in the middle of the twentieth century [1] and more recently evolved with the work of Rowe and Kahn [2,3] to encompass a more socially engaged and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Several studies confirmed the importance of communication and social support for the health and well being in aged people (Bryant et al, 2001;Cannuscio, Block, & Kawachi, 2003;Dunér & Nordströ m, 2005;Kwong & Kwan, 2007;McCann Mortimer, Ward, & Winefield, 2008;Nagalingam, 2007;Nicholson, 2009). Access to social capital (resources available to individuals and groups through social connections and social relations with others) enables older women to maintain productive, independent, and fulfilling lives.…”
Section: Coping Strategies Of Iranian Elderly Women 583mentioning
confidence: 81%
See 1 more Smart Citation
“…Several studies confirmed the importance of communication and social support for the health and well being in aged people (Bryant et al, 2001;Cannuscio, Block, & Kawachi, 2003;Dunér & Nordströ m, 2005;Kwong & Kwan, 2007;McCann Mortimer, Ward, & Winefield, 2008;Nagalingam, 2007;Nicholson, 2009). Access to social capital (resources available to individuals and groups through social connections and social relations with others) enables older women to maintain productive, independent, and fulfilling lives.…”
Section: Coping Strategies Of Iranian Elderly Women 583mentioning
confidence: 81%
“…Religious activities bring tangible results in physical and mental health-reflecting the religiosity perspective, and they are seen as means of aging successfully (Nagalingam, 2007). Religion and spirituality are also important to the well being of older adults (McCann Mortimer et al, 2008). Furthermore, some studies have shown that religion and spirituality facilitate the acceptance of death and reduce the fear of death and future concerns (Caldas & Bertero, 2007;McCann Mortimer et al, 2008).…”
Section: Coping Strategies Of Iranian Elderly Women 583mentioning
confidence: 97%
“…If any dimension of functioning (physical, cognitive or social) worsens, interviewees would like to apply psychological mechanisms or to change their living circumstances in order to cope with that loss. If they cannot maintain their quality of life in relation to autonomy and independence in this process, then they wish for quality of death as a successful ending to life (McCann Mortimer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on successful aging have frequently discussed the role of spirituality in the process of life and old age, but findings vary (McCann Mortimer, Ward, & Winefield, 2008;Parker et al, 2002). Spirituality has been referred to in many studies as a "forgetting factor" (Crowther, Parker, Achenbaum, Larimore, & Koenig, 2002).…”
Section: A Harmonious and Balanced Lifementioning
confidence: 99%
“…As Matsubayashi et al (2006) observed, differences in the ratings of the items may be the result of differences in values between cultures given that the successful ageing attributes were identified from published Western literature. The meanings of successful ageing among older adults are therefore much more diverse (McCann Mortimer, Ward & Winefield, 2008).…”
Section: Resultsmentioning
confidence: 99%